Growth of a mangrove (Rhizophora apiculata) seedlings as influenced - Kathiresan, K (2002)
The growth performance of Rhizophora apiculata Blume (mangrove) seedlings in the presence and absence of exogenous gibberellic acid (GA3) under different combinations of salinity and light was analyzed. Root and shoot growth responses of 75-day old seedlings in liquid-culture, were measured. It was concluded that light exhibited a significant inhibitory effect on all the growth parameters-number of primary roots, primary root length, shoot elongation, number of leaves, total leaf area; and, the GA3 treatment singly or in combinations with light, showed a significant influence on the total leaf area and primary root length